2015
DOI: 10.1088/0004-637x/806/1/97
|View full text |Cite
|
Sign up to set email alerts
|

Polarization in Exoplanetary Systems Caused by Transits, Grazing Transits, and Starspots

Abstract: We present results of numerical simulations of flux and linear polarization variations in transiting exoplanetary systems, caused by the host star disk symmetry breaking. We consider different configurations of planetary transits depending on orbital parameters. Starspot contribution to the polarized signal is also estimated. Applying the method to known systems and simulating observational conditions, a number of targets is selected where transit polarization effects could be detected. We investigate several … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…This transit polarization effect has been investigated for planets transiting cool stars by Carciofi & Magalhaes (2005) and Kostogryz et al (2011). Kostogryz et al (2015) have calculated the transit polarization for a range of transiting planets, and shown that the size of the effect increases for lower stellar temperatures, lower gravities, and larger planet to star radius ratios, with the effect reaching up to 10 ppm or more at 400 nm in the most favourable cases. However, WASP-18 is outside the range of parameters considered in that study.…”
Section: Transit Polarimetrymentioning
confidence: 99%
“…This transit polarization effect has been investigated for planets transiting cool stars by Carciofi & Magalhaes (2005) and Kostogryz et al (2011). Kostogryz et al (2015) have calculated the transit polarization for a range of transiting planets, and shown that the size of the effect increases for lower stellar temperatures, lower gravities, and larger planet to star radius ratios, with the effect reaching up to 10 ppm or more at 400 nm in the most favourable cases. However, WASP-18 is outside the range of parameters considered in that study.…”
Section: Transit Polarimetrymentioning
confidence: 99%
“…Besides limb darkening, continuum radiation also carries some small degree of polarization; this depends on the wavelength and could be detected in exoplanet transit polarimetry (Kostogryz et al 2015(Kostogryz et al , 2016Wiktorowicz & Laughlin 2014).…”
Section: Exoplanet Detection Limitsmentioning
confidence: 99%
“…The value of this polarization is maximal when the planet is crossing the edge of the source (Carciofi & Magalhães 2005;Wiktorowicz & Laughlin 2014;Kostogryz et al 2015). However, the occultation happens for phase angles greater than 90…”
Section: Polarization Due To the Stellar Occultation By Planetmentioning
confidence: 97%